Antifungal effects and biocontrol potential of lipopeptide-producing Streptomyces against banana Fusarium wilt fungus Fusarium oxysporum f. sp. cubense - Wang, Xiaxia; Du, Zhenghua; Chen, Chanxin; Guo, Shuang; Mao, Qianzhuo; Wu, Wei; Wu, Ruimei; Han, Wenbo; Xie, Peifeng; Zeng, Yiping; Shan, Wenna; Wang, Zonghua; et al. (Frontiers in Microbiology, 2023)
Fusarium wilt of banana (FWB), caused by Fusarium oxysporum f. sp. cubense (Foc), especially tropical race 4 (TR4), presents the foremost menace to the global banana production. Extensive efforts have been made to search for efficient biological control agents for disease management. Our previous study showed that Streptomyces sp. XY006 exhibited a strong inhibitory activity against several phytopathogenic fungi, including F. oxysporum. Here, the corresponding antifungal metabolites were purified and determined to be two cyclic lipopeptide homologs, lipopeptin A and lipopeptin B. Combined treatment with lipopeptin complex antagonized Foc TR4 by inhibiting mycelial growth and conidial sporulation, suppressing the synthesis of ergosterol and fatty acids and lowering the production of fusaric acid. Electron microscopy observation showed that lipopeptide treatment induced a severe disruption of the plasma membrane, leading to cell leakage. Lipopeptin A displayed a more pronounced antifungal activity against Foc TR4 than lipopeptin B. In pot experiments, strain XY006 successfully colonized banana plantlets and suppressed the incidence of FWB, with a biocontrol efficacy of up to 87.7%. Additionally, XY006 fermentation culture application improved plant growth parameters and induced peroxidase activity in treated plantlets, suggesting a possible role in induced resistance. Our findings highlight the potential of strain XY006 as a biological agent for FWB, and further research is needed to enhance its efficacy and mode of action in planta.